Research Results of the Earth Dam Condition of Cooling Pond of the Zaporizhzhia Nuclear Power Plant - Ulianov, V. Y; Bilyk, V. V (Science and Transport Progress, 2022)
Purpose. The work is aimed to determine the real location in space and conduct possible measurement of the true geometric dimensions of the NPP cooling pond dam, especially its underwater part and to detect the additional and previously unaccounted factors that could affect these parameters, as well as the state of the entire structure in general. Methodology. A comprehensive analysis of all available materials about engineering surveys and geotechnical studies was carried out at the dam of the cooling pond of the Zaporizhzhia NPP. Due to this, a more comprehensive look at the results of engineering and geological surveys was obtained. Findings. The state of soils in the body of the earth dam can be influenced by weakened and poorly studied zones of the dam. These zones were determined based on the analysis of the soil studies data of the dam’s ground. Previously uncovered issues on the operation of the facility were raised and considered. The ways and methods for additional study of the earth dam of the cooling pond were selected, the conditions for their use were substantiated. A numerical relationship between the thickness of loose soils and the amount of surface subsidence were determined for the first time. A generalized geological section of the dam body was compiled for further modeling of geotechnical processes. Originality. For the first time since construction, a comprehensive program was developed for assessing the technical condition of the cooling pond dam using innovative methods from the Laboratory of Research of Nuclear and Thermal Power Plants in Prydniprovska State Academy of Civil Engineering and Architecture (PSACEA). In particular, combined hydrographic-geodetic and aerovisual methods were proposed using specially designed universal leading signs that have no analogues in world practice. Practical value. The application of the developed comprehensive program using innovative methods allows assessing the technical condition of the cooling pond dam of the NPP.